The Possibilities of Scintigraphic Visualization of Surfactants in the Lung of the Rat - Koren, E.; Filjak, K.; Gadže, A.; Spaventi, Š. (Nuklearmedizin - NuclearMedicine, 1980)
Incorporation of radioactive iodine into the surfactant system of the rat lung has been studied. Specially prepared particles labelled by 125I-oleic acid or 131I-oleic acid were injected intravenously and the distribution of radioiodine in the body of the animals was observed at various time intervals by means of a gamma camera and a gamma counter. The results showing appreciable accumulation of isotope in the lungs and the surfactant phospholipids, constitute a basis for the development of a new scintigraphic method for studying metabolic functions and morphology of the lung.